2019
DOI: 10.1159/000497184
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Neutrophil-to-Lymphocyte Ratio Was a Predictor of Lymph Node Metastasis in Endometrial Cancer Patients

Abstract: Objective: The pretreatment neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) have been reported to be useful as markers for prognostic factors and metastasis in several cancers. The aim of this study was to identify the predictor of lymph node (LN) metastasis by pretreatment NLR and PLR in patients with endometrial cancer. Methods: Medical charts of the patients with endometrial cancers that received primary surgery at our hospital between 2007 and 2013 were retrospectively analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
2
37
3
Order By: Relevance
“…The worse prognosis associated with higher PLR might also reflect an important role of platelet dominant inflammation response in the process of lymph node metastasis in CRC, except for the neutrophil dominant inflammation effects that were confirmed by NLR in a previous study. 22 Moreover, we also found that T4 stage and N stages were independent prognosis factors in stage III CRC patients, which is consistent with the latest NCCN guideline recommendations 23 and previous reports. 24,25 P-glycoprotein (P-GP), a member of the ATP binding box (ABC) superfamily, extrudes chemotherapeutic drugs out of cells.…”
Section: Dovepresssupporting
confidence: 91%
“…The worse prognosis associated with higher PLR might also reflect an important role of platelet dominant inflammation response in the process of lymph node metastasis in CRC, except for the neutrophil dominant inflammation effects that were confirmed by NLR in a previous study. 22 Moreover, we also found that T4 stage and N stages were independent prognosis factors in stage III CRC patients, which is consistent with the latest NCCN guideline recommendations 23 and previous reports. 24,25 P-glycoprotein (P-GP), a member of the ATP binding box (ABC) superfamily, extrudes chemotherapeutic drugs out of cells.…”
Section: Dovepresssupporting
confidence: 91%
“…Previous studies of endometrial cancer have suggested that the presence of pretreatment leukocytosis or thrombocytosis is associated with an advanced clinical stage and is an independent predictor of decreased survival 10–14,16,17 . The present results showed, however, that women who had only leukocytosis or only thrombocytosis had a favorable prognosis; in other words, they had survival rates equivalent to those of women with normal leukocyte/platelet counts.…”
Section: Discussioncontrasting
confidence: 75%
“…To our knowledge, eight retrospective studies have investigated the significance of elevated leukocyte and platelet counts among women with endometrial cancer (Table ) 10–13 . Of these, four studies used higher leukocyte count and higher platelet count as prognostic variables, 10,11,14,15 whereas the other four used higher neutrophil‐to‐lymphocyte ratio (NLR) and higher platelet‐to‐lymphocyte ratio (PLR) 12,13,16,17 . Seven of the eight studies investigated the prognostic significance of elevated leukocyte count (or increased NLR) and elevated platelet count (or increased PLR) separately, 10–12,14–17 and most found that both leukocytosis (or increased NLR) and thrombocytosis (or increased PLR) are associated with advanced clinical stage or poor prognosis 10–12,14,16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, one concerning cervical cancer was disposed separately cause of providing HRs and survival outcomes for patients with two different treatments [21]. As a consequence, fifteen, nine, and four publications regarding to cervical [19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34], ovarian [35][36][37][38][39][40][41][42][43], and endometrial cancer [44][45][46][47] were enrolled, respectively.…”
Section: Literature Search Results and Characteristicsmentioning
confidence: 99%